Fermentation quality, amino acids profile, and microbial communities of whole-plant soybean silage in response to Lactiplantibacillus plantarum B90 alone or in combination with functional microbes - Jin, Sijie; Tahir, Muhammad; Huang, Fuqing; Wang, Tianwei; Li, Huangkeyi; Shi, Weixiong; Liu, Yayong; Liu, Weichun; Zhong, Jin (Frontiers in Microbiology, 2024)
Promoting the availability of silage with a high protein content on farms can lead to profitable and sustainable ruminant production systems. Whole plant soybean (Glycine max L. Merrill, WPS) is a promising high-protein forage material for silage production. In this study, we investigated the fermentation quality, amino acids profile and microbial communities of WPS silage in response to inoculation of lactic acid bacteria (LAB) alone or in combination with non-LAB agents. Before preparing the treatments, the chopped WPS was homogenized thoroughly with 0.3% molasses (0.3 g molasses per 100 g fresh matter). The treatments included CK (sterilized water), LP (Lactiplantibacillus plantarum B90), LPBS (LP combined with Bacillus subtilis C5B1), and LPSC (LP combined with Saccharomyces cerevisiae LO-1), followed by 60 days of fermentation. The inoculants significantly decreased the bacterial diversity and increased the fungal diversity of WPS silage after ensiling. As a result, the contents of lactic acid and acetic acid increased, while the pH value and propionic acid content decreased in the inoculated silages. The amino acids profile was not influenced by inoculants except phenylalanine amino acid, but LP and LPSC silages had substantial greater (p < 0.05) relative feed values of 177.89 and 172.77, respectively, compared with other silages. Taken together, the inoculation of LP alone or in combination with BS was more effective in preserving the nutrients of WPS silage and improve fermentation quality.